INTERDISCIPLINARY TASKS: CONCEPTIONS OF ELEMENTARY TEACHERS (Revista Lusófona de Educação, 2026)
Interdisciplinarity has been discussed in the field of educational sciences for several decades, consistently recognized for its pedagogical relevance and potential. Nevertheless, its effective integration into teaching and learning practices remains limited, particularly in primary education. This issue is especially pertinent in the context of the 1st cycle of basic education in Portugal, where the monoteaching model theoretically offers more favorable conditions for interdisciplinary approaches. Despite this potential, significant challenges persist in the operationalization of interdisciplinary teaching. One major barrier is the conceptual ambiguity surrounding interdisciplinarity itself, with varying interpretations among educators, which hampers its consistent application. In order to explore the conceptions held by teachers regarding interdisciplinary tasks, a quantitative study was conducted involving 74 primary school teachers. The data reveal a wide range of understandings concerning the nature and scope of interdisciplinarity. Additionally, the findings suggest that teachers identify particular curricular domains where interdisciplinary work is perceived as more achievable and meaningful, highlighting the need for clearer guidance and professional development in this area.